Audit of open pediatric tracheostomies at the university college hospital, Ibadan (2020)
Background: Tracheostomy is the creation of a communication between the trachea and the overlying skin, maintained by a tube. This is done either by an open or percutaneous technique. Anatomical and physiological variation of the paediatric trachea and adjoining structures necessitates finite skills and consistent competence in performing pediatric tracheostomies, lack of which may cause higher mortality and morbidity outcome in tracheostomies in the pediatric age group. Objectives: There are inadequate local data on the outcomes of pediatric tracheostomies; therefore, we conducted a local audit of pediatric tracheostomy to describe our experience. Methods: A retrospective study of pediatric patients who had tracheostomies from June 2011 to December 2017 was done. Results: Thirty‑four patients were identified, all of whom had an open tracheostomy. The age range was 3 weeks to 16 years; M: F ratio was 2.4:1. Indications for surgery were obstructive (88.2%) and prolonged‑assisted intubation (11.8%). Recurrent respiratory papillomatosis, retropharyngeal abscess, and foreign‑body aspiration were the main obstructive causes. Three patients (8.8%) had repeat procedures, and these patients were initially discharged on tracheostomy tube and instructions were given for home care. Conclusion: Despite the evolving local challenges peculiar to clinical practice in developing countries, the outcome of pediatric tracheostomy in our hospital is good